Rapid, simple, low-cost smartphone-based fluorescence detection of Escherichia coli - Rojas-Barboza, Dante; Park, Edward; Sassenfeld, Rolfe; Winder, Jeremy; Smith, Geoffrey B.; Valles-Rosalles, Delia; Delgado, Efren; Park, Young Ho (International Journal of Agricultural and Biological Engineering, 2021)
Food and waterborne diseases pose considerable public health threats even in highly industrialized parts of the world. Examples of these pathogens in food can be Escherichia coli O157: H7, Salmonella sp., and Listeria monocytogenes. Rapid, reliable detection of pathogens mitigates serious health problems and economic losses due to outbreaks and robust tests safeguard the food supply. In this study, a smartphone-based apparatus was employed to demonstrate quantitative detection of E. coli. To validate the applicability of the present smartphone-based fluorescence device, RNA was extracted from the E. coli K-12 strain and amplified using two different primers (dnaK and rpoA) via quantitative polymerase chain reaction (qPCR). Serial dilutions of RNA from 10 to 0.0001 ng/µL were prepared at the start of the PCR amplification and the PCR products were detected by CYBR Green1-based fluorescence. For a proof-of-concept test for the smartphone system, samples from these PCR products were then analyzed. The detection system employed a novel algorithm to analyze fluorescence signals and read changes in E. coli DNA concentration. The correlations between the fluorescence percentage and DNA concentrations were R=0.945 for the dnaK primer and R=0.893 for the rpoA primer, respectively. Utilizing this new fluorescent analysis technique resulted in comparable accuracy to the real-time PCR fluorescent signal detection. The key innovation of this approach was to combine efficient image processing encoded into a smartphone application with a low-cost 3-D printed device that allowed quantification of bacterial nucleic acid. Keywords: smartphone, fluorescence, E. coli, low-cost, 3D-Print DOI: 10.25165/j.ijabe.20211403.5865 Citation: Rojas-Barboza D, Park E, Sassenfeld R, Winder J, Smith G B, Valles-Rossalles D, et al. Rapid, simple, low-cost smartphone-based fluorescence detection of Escherichia coli. Int J Agric & Biol Eng, 2021; 14(3): 189–193.